Carbon tattooing of axillary lymph nodes in breast cancer patients before neoadjuvant chemotherapy: A retrospective analysis. Issue 3 (June 2023) - Porpiglia, Mauro; Borella, Fulvio; Chieppa, Pierluigi; Brino, Carola; Ala, Ada; Marra, Vincenzo; Castellano, Isabella; Benedetto, Chiara
Background: This study aimed to investigate the feasibility and accuracy of tattooing suspicious axillary lymph nodes with carbon suspension at the time of breast cancer (BC) diagnosis and the intraoperative correspondence between tattooed lymph node (TLN) and sentinel lymph node (SLN) in patients who underwent neoadjuvant chemotherapy (NACT). Methods: In this retrospective study, we analyzed consecutive BC patients who underwent NACT, between April 2019 and May 2021, at the Breast Unit of Sant'Anna Hospital in Turin, Italy. Before NACT, all suspicious biopsied lymph nodes were marked with carbon suspension. All SLNs, TLNs, and axillary nodal dissection specimens were sent for histopathological examination. Results: The study group included a total of 49 patients with BC. The overall identification rate of TLNs was 83.7% (41/49; 95%, confidence interval - CI 0.70-0.92). In patients who underwent target axillary dissection (TAD) the carbon tattooing had an intraoperative identification rate of 84.4% (27/32; 95% CI 0.67-0.95) while, in the case of axillary lymph node dissection, TLNs were detected in 82.3% (14/17; 95% CI 0.56-0.96) of patients. The correlation between TLN and SLN was 71.8% (23/32). Conclusions: These results confirmed that tattooing axillary lymph nodes has an acceptable identification rate. We also confirmed that this procedure, in addition to SLN biopsy, improves the accuracy of surgical axillary staging.